2017
DOI: 10.1038/jhh.2016.99
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of home blood pressure telemonitoring: a systematic review and meta-analysis of randomised controlled studies

Abstract: To summarise evidence about the effectiveness of home blood pressure telemonitoring (HBPT) and identify the key components of intervention. We comprehensively searched PubMed, EMBASE and the Cochrane Library for relevant studies. The authors were contacted for additional information. Two authors independently extracted the data and assessed the risk of bias. 46 randomised controlled trials including a total of 13 875 cases were identified. Compared with usual care, HBPT improved office systolic blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 57 publications
4
108
0
9
Order By: Relevance
“…Recently, an updated meta‐analysis of 46 randomized controlled trials with 13 875 cases confirmed the superiority of BPT on usual care in terms of improvement of BP control, although the results of this meta‐analysis should be considered with some caution given the occurrence of many mistakes in the selection and interpretation of the included studies. This meta‐analysis, in the context of its limitations, showed low‐strength evidence of efficacy of BPT for surrogate outcomes, whereas it suggested that longer‐term (6 to 12 months vs <6 months) home BPT accompanied by counseling support from study personnel may result in lower BP values.…”
Section: Clinical Efficacy Of Bptmentioning
confidence: 99%
“…Recently, an updated meta‐analysis of 46 randomized controlled trials with 13 875 cases confirmed the superiority of BPT on usual care in terms of improvement of BP control, although the results of this meta‐analysis should be considered with some caution given the occurrence of many mistakes in the selection and interpretation of the included studies. This meta‐analysis, in the context of its limitations, showed low‐strength evidence of efficacy of BPT for surrogate outcomes, whereas it suggested that longer‐term (6 to 12 months vs <6 months) home BPT accompanied by counseling support from study personnel may result in lower BP values.…”
Section: Clinical Efficacy Of Bptmentioning
confidence: 99%
“…Использование данной технологии способствует снижению загруженности участковых терапевтов и одновременно увеличивает охват диспансерным наблюдением больных с ГБ. Телемедицинские технологии существенно повышают эффективность антигипертензивной терапии и приверженность больных к лечению благодаря регулярным контактам пациента с врачом, в том числе, и с помощью телефонной связи [6][7][8]. На сегодняшний день имеется достаточный международный и отечественный опыт, нормативно-методическая база и доступное оборудование, что позволяет повсеместно расширять практику дистанционного наблюдения за больными ГБ [6].…”
Section: Blood Pressure Remote Monitoring дистанционный мониторинг арunclassified
“…In addition to being a significant prognostic indicator of target organ damage, cardiovascular mortality and cardiovascular events,61 HBP monitoring can be supplemented with telemonitoring, incorporating recent advances in digital technology to enable patient-clinician feedback. Meta-analyses have shown that HBP telemonitoring can improve BP control,62 and that the provision of additional support (e.g. counselling, education, behavioural management and adherence contracts) may have an additive beneficial effect, but did not reach statistical significance 62.…”
Section: Hbp Monitoringmentioning
confidence: 99%
“…Meta-analyses have shown that HBP telemonitoring can improve BP control,62 and that the provision of additional support (e.g. counselling, education, behavioural management and adherence contracts) may have an additive beneficial effect, but did not reach statistical significance 62. Home telemonitoring is also associated with increased prescribed medications, changes in behaviour such as self-reported salt intake, improved medicines adherence63 64 and appears well-tolerated 65…”
Section: Hbp Monitoringmentioning
confidence: 99%